Vitamin A Supplementation as an Intervention for Reducing Stunting in Young Children in Coastal Regions of Indonesia - Listy Handayani; Muhammad Amin; Wartina Karamelka (Journal of Epidemiology and Health Science, 2025)
Background: Stunting is a manifestation of impaired growth and development in children, primarily caused by chronic malnutrition, recurrent infections, and insufficient psychosocial stimulation. Vitamin A deficiency is recognized as a major contributing factor to stunting due to its critical role in supporting immune function and enhancing resistance to infections. Although global initiatives have aimed to combat vitamin A deficiency, its specific impact on reducing stunting particularly in coastal regions with limited access to nutritious food and healthcare remains insufficiently examined. Objective: This study aims to analyze the role of vitamin A supplementation as a public health intervention for reducing stunting in young children, with a particular focus on coastal areas where nutritional and healthcare challenges are more prevalent. Methods: This study utilized a systematic literature review methodology, employing the keywords "vitamin A," "stunting," and "supplementation" to search academic databases including Google Scholar, NCBI, PubMed, and Mendeley. Articles were screened for relevance and methodological rigor, focusing on studies that investigated the association between vitamin A supplementation and child growth, especially in relation to stunting. After applying defined inclusion and exclusion criteria, a total of 20 relevant articles 13 national and 7 international were selected for comprehensive analysis. Results: The review indicates that vitamin A supplementation has a protective effect against stunting, particularly in children not suffering from chronic malnutrition. Studies demonstrate a strong association between vitamin A deficiency and increased prevalence of stunting, especially among low-income and nutritionally vulnerable populations. Moreover, interventions combining vitamin A supplementation with a micronutrient-rich diet yield superior outcomes in reducing stunting incidence. However, research specifically focused on coastal populations remains limited, making it difficult to draw definitive conclusions about the effectiveness of vitamin A supplementation in these settings. Conclusion: Vitamin A supplementation contributes significantly to reducing the prevalence of stunting, particularly when integrated with comprehensive nutritional support. Nevertheless, its effectiveness is influenced by multiple factors, including socioeconomic status, parental education, food security, and healthcare accessibility. Further research is essential to assess the specific impact of vitamin A interventions in coastal areas, and to develop integrated strategies that incorporate nutrition education, dietary improvement, and strengthened health service delivery. Keywords: Vitamin A, Stunting, Supplementation, Child Nutrition, Coastal Areas, Indonesia.